Fragmenting the gaze - Bokulich, Claudia, author; Osborne, Erika, advisor; Lajarin-Encina, Aitor, advisor; Ryan, Ajean, committee member; DeMirjyn, Maricela, committee member (Colorado State University. Libraries, 2025)
In my figurative paintings, I utilize narrative fragmentation and compositional simultaneity to explore cultural constructs of gender roles, femininity, vanity, and consumerism in contemporary life. My work often highlights the absurdities of human behavior, playfully critiquing these patterns while simultaneously acknowledging the grace of the human condition. Engaging with elements of art history, I employ narrative fragmentation as a tool to reflect contemporary societal structures while also recognizing historical patterns. In the following sections, I will begin by defining narrative fragmentation, first in literary terms and then in relation to fine art. I will discuss how narrative fragmentation has become a popular tool in artmaking over the last century, serving as a commentary on society, and I will highlight specific artists who embrace this approach. I will analyze the compositional strategies in the works of these artists in conjunction with my own, identifying both similarities and differences in content and themes. By adopting a feminist approach to painting, I aim to challenge the male gaze and the tropes that male artists have employed throughout art history. To strengthen my investigation, I will highlight contemporary female artists who share this goal. Together with these artists, I advocate for dismantling gender norms and reclaiming the female figure. I argue that while female nudity is a prominent feature in my paintings, it does not adhere to the objectification typically linked to the male gaze. Although the male gaze may never be entirely eradicated, it can be effectively challenged. By referencing influential feminist art critics and artists, I emphasize the importance of acknowledging the female experience, with my paintings serving as representations of these experiences.